Effects of modified reverse sural neurocutaneous flap repair on wound healing in patients with soft tissue defects of the foot and ankle - Shun Hong Luo; Yong Ping Li; Man Hua Liu; Yu Xie; Jian Li; Hao Yu; Chun Hua He (Journal of Orthopaedic Surgery and Research)
Abstract Objective The surgical team in this study examined the efficacy of a modified reverse sural neurocutaneous flap repair in treating soft tissue defects of the ankle and foot caused by accidents. Methods This study enrolled 89 patients treated for soft tissue defects of the ankle or foot between January 2007 and December 2023. The patients were divided into two groups: 44 patients underwent a modified reverse sural neurocutaneous flap repair, while 45 received traditional treatment. The modified technique involved repairing various anatomical structures, including fascia, the saphenous nerve, the great saphenous vein, subcutaneous tissue, and skin, with flap sizes ranging from 14 to 152 cm². In the traditional treatment group, the distal perforator of the peroneal artery was identified 5 cm above the lateral malleolus. Island fasciocutaneous flaps were designed along the sural nerve and lesser saphenous vein, elevated subfascially, rotated 180 degrees, and inset without tension. Donor sites were closed with grafts or direct sutures. Results Of the 44 patients, who underwent the modified technique, 35 were male and 9 were female. Follow-up periods ranged from 2 to 24 weeks to monitor outcomes and recovery. The average size of the affected soft tissue was 71 cm2. Thirty-nine flaps survived completely, while three experienced partial necrosis and two had marginal necrosis. No cases of severe venous congestion were reported. The complication rate was lower with the modified method compared to the traditional repair (p < 0.05). Conclusion The modified reverse neurocutaneous flap repair is a reliable and structured approach to treating soft tissue defects of the ankle and foot. This method has demonstrated favorable patient outcomes and presents a promising avenue for future studies and clinical practice.